PENGENDALIAN KUALITAS BATUBARA SEAM 300 BERDASARKAN PARAMETER KUALITAS BATUBARA DARI FRONT SAMPAI KE BUYER DI PT KUANSING INTI MAKMUR, JOB SITE TANJUNG BELIT, BUNGO, JAMBI - Hafiz Zakwan; Heri Prabowo (Departemen Teknik Pertambangan FT UNP, 2021)
Abstract. Coal quality control is an activity in controlling coal quality, because during the mining process until it reaches the buyer, there is a decline in coal quality. The coal mining activity was carried out in the west block at the East Pit of PT Kuansing Inti Makmur. This study was conducted to determine changes in coal quality, determine what factors cause changes in coal quality, and efforts in handling changes in coal quality with parameter values used, namely total water content (TM), ash content (Ash), and calorific value (GCV arb). Based on the results of the analysis of coal quality, there are changes when coal is transported to the stockpile from the front coal getting with the highest quality change, namely at seam 300 CR3 (TM = 4.06%, ASH = 0.23%, GCV = -303 Kcal/Kg ) and seam 300 LOWER (TM = 1.70%, ASH = 0.82%, GCV = -174 Kcal/Kg). And the results of the analysis of changes in coal quality when transported from the stockpile to the buyer there are changes when the coal arrives at the buyer with a change value of TM = 1.64%, ASH = 0.32%, GCV = -92 Kcal/Kg.